Basic Education Transformations: Steps To Breakthrough In Improving Numeracy Literacy In Elementary Schools - Akmal, Ihwanul; Waningyun, Prissilia Prahesta (Universitas Pahlawan Tuanku Tambusai, 2024)
Primary education shapes students' academic foundations and skills, directly impacting their future success. Improving literacy and numeracy at the primary school level in Indonesia remains a pressing issue. Despite various initiatives and policies being implemented, data shows that primary school students' literacy and numeracy levels often need to meet the expected standards. This study uses a qualitative method with a descriptive approach to the effectiveness of the Campus Teaching VI Program in improving literacy and numeracy at SD Negeri III, Selanegara. This research includes observation, interview, documentation, and pretest and post-test stages. After the school observation process and interviews with the school, it was found that the level of literacy and numeracy at SD Negeri III, Selanegara, was still in the below-average category. In connection with these results, various programs were immediately arranged to improve the quality of literacy and numeracy of SD Negeri III, Selanegara students. Based on the research results on the Teaching Campus's effectiveness in enhancing numeracy literacy at SD Negeri III, Selanegara, this program has succeeded in achieving its objectives well. The implementation of the Teaching Campus Program showed significant improvement, as seen from the comparison between pretest and post-test scores. The interventions, including literacy guidance, reading corner arrangement, library improvement, and reading park provision, proved effective in improving the quality of learning and student skills.